Pengaruh Pemberian Pupuk Organik Cair Cangkang Telur Ayam Boiler dan Pupuk Anorganik Urea Terhadap Pertumbuhan dan Hasil Tanaman Bayam Merah (Amaranthus tricolor L.) Varietas Mira - Tri Fatmawati; Muharam Muharam; Wagiono Wagiono (Jurnal Ilmiah Wahana Pendidikan, 2021)
Red spinach is a vegetable plant that has high economic value and is usually consumed by the leaves. In 2019 there was a decrease caused by the lack of soil fertility so that to increase production, it could improve soil fertility by means of fertilization.The purpose of this study was to obtain the optimal combination dose of organic chicken eggshell fertilizer from inorganic urea fertilizer on the growth and yield of red spinach (Amaranthus tricolor L.) mira variety. The research was carried out from June to July 2021, on the exact land in Pasir jengkol Village, Majalaya District, Karawang Regency, West Java. The research method used was factorial randomized block design (RAK), the first factor was liquid organic fertilizer chicken egg shells (C) consisting of 3 levels: c0 (0 ml/L), c1 (30 ml/L), c2 (60 ml/L). L) and the second factor of inorganic fertilizer urea (u) consists of 3 levels: u0 (0 kg/ha), u1 (50 kg/ha), u2 (100 kg/ha).There were 9 treatments with 3 replications so there were 27 experimental units. The results showed that there was no interaction between the addition of liquid organic fertilizer chicken egg shells with inorganic fertilizers on the growth and yield of red spinach (Amaranthus tricolor L.) mira variety. There was no one dose of inorganic urea fertilizer that provided optimal growth and yield of red spinach (Amaranthus tricolor L.) mira variety for each dose of liquid organic fertilizer given chicken egg shells.